Routine coagulation testing in intensive care - Musca, S.; Desai, S.; Roberts, B.; Paterson, T.; Anstey, Matthew (Australasian Academy of Critical Care Medicine, 2016)
© 2016, Australasian Medical Publishing co. All Rights Reserved.Objective: To test a simple clinical guideline to reduce unnecessary routine testing of coagulation status. Design, setting and participants: A prospective, unblinded, observational study of coagulation testing frequency before and after introduction of a simple clinical guideline. We included 253 patients admitted to a tertiary intensive care unit: 100 patients consecutively enrolled before our intervention (May - July 2015) and 153 patients consecutively enrolled after our intervention (August - September 2015). Intervention: We introduced a clinical guideline and educational program in the ICU from 18 August 2015. Main outcome measures: The number of coagulation tests performed per patient bed-day, and the associated pathology costs. Results: Over the 3-month sample period, 999 coagulation profiles were performed for 253 patients: 720 (72%) in 100 patients before, and 279 (28%) in 153 patients after our intervention. The testing frequency fell from 1.12 to 0.41 per patient bed-day (P < 0.001). A total of 463 pre-intervention coagulation profiles (64%) were classified as unnecessary, and the cost of all coagulation tests fell by 60.5% per bed-day after the intervention. Conclusion: A simple clinical guideline and educational package reduced unnecessary coagulation tests and costs in a tertiary referral ICU.